Bus-Protection Device-Tank-type Vehicle System Collision Research. Issue 1 (January 2020) - Zhang, Guosheng; Zheng, Haiyang; Chen, Ye; Liu, Hongli
Abstract: Aiming at the problem of insufficient protective performance of the rear protection device, a new type of rear protection device with high protective performance is proposed and designed. A new type of tank-type vehicle rear protection device is used to establish the collision environment of bus- protection devices- tank-type vehicle system collision, and the dynamic response characteristics of the collision system were simulated and analyzed. The safety of the rear protection device was analyzed and evaluated by the real bus impacting tank-type vehicle, and compared with the simulation results. The research result shows that the protective performance of the square tube protection device is effective.